Distribution and dynamics of epidemic and pandemic Vibrio parahaemolyticus virulence factors - Ceccarelli, Daniela; Hasan, Nur A.; Huq, Anwar; Colwell, Rita R. (Frontiers in Cellular and Infection Microbiology, 2013)
Vibrio parahaemolyticus, autochthonous to estuarine, marine, and coastal environments throughout the world, is the causative agent of food-borne gastroenteritis. More than 80 serotypes have been described worldwide, based on antigenic properties of the somatic (O) and capsular (K) antigens. Serovar O3:K6 emerged in India in 1996 and subsequently was isolated worldwide, leading to the conclusion that the first V. parahaemolyticus pandemic had taken place. Most strains of V. parahaemolyticus isolated from the environment or seafood, in contrast to clinical strains, do not produce a thermostable direct hemolysin (TDH) and/or a TDH-related hemolysin (TRH). Type 3 secretion systems (T3SSs), needle-like apparatuses able to deliver bacterial effectors into host cytoplasm, were identified as triggering cytotoxicity and enterotoxicity. Type 6 secretion systems (T6SS) predicted to be involved in intracellular trafficking and vesicular transport appear to play a role in V. parahaemolyticus virulence. Recent advances in V. parahaemolyticus genomics identified several pathogenicity islands (VpaIs) located on either chromosome in both epidemic and pandemic strains and comprising additional colonization factors, such as restriction-modification complexes, chemotaxis proteins, classical bacterial surface virulence factors, and putative colicins. Furthermore, studies indicate strains lacking toxins and genomic regions associated with pathogenicity may also be pathogenic, suggesting other important virulence factors remain to be identified. The unique repertoire of virulence factors identified to date, their occurrence and distribution in both epidemic and pandemic strains worldwide are described, with the aim of highlighting the complexity of V. parahaemolyticus pathogenicity as well as its dynamic genome.